Pelatihan Pembuatan Film di Omah Gondhol Yogyakarta - Rr. Pramesthi Ratnaningtyas; Ikhwan Afif Mahbubi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This Community Service Activity aims to integrate cultural values ​​such as gamelan and keroncong into film works. In addition, to introduce cultural heritage to the younger generation. Activities include training and film screenings. Activities are carried out together with students, divided into several divisions with implementation stages including pre-implementation, implementation and post-implementation. Evaluation of the activity showed an increase in information or insight of 34 points related to script writing, as well as 15 and 13 points of understanding of material related to camera operation and editing. In this activity, the team also made a company profile video that already has Intellectual Property Rights (IPR) at the Directorate General of Intellectual Property. In the future, there needs to be other art and cultural productions through films. Then from the films that have been produced are promoted or introduced more widely using social media.